Pengaruh Persepsi Mahasiswa Terhadap Minat Memilih Profesi Sebagai Akuntan Publik - Riani Sukma Wijaya; Fajrul Falakh; Riri Putri Dika (Jurnal Ekonomi dan Bisnis Dharma Andalas, 2023)
This study aims to determine and analyze: (1) the effect of financial rewards on the interest in choosing a profession as a public accountant, (2) the effect of professional training on the interest in choosing a profession as a public accountant, (3) the influence of social values ​​on the interest in choosing a profession as an accountant. the public, (4) the influence of the work environment on the interest in choosing a profession as a public accountant, and (5) the effect of labor market considerations on the interest in choosing a profession as a public accountant. The type of research used in this research is quantitative research. This study uses a population of undergraduate students in Accounting, Faculty of Business and Economics, Dharma Andalas University. This study used a sample of S1 students from the 2018 2019 class of Accounting Department, Faculty of Business and Economics, Dharma Andalas University, which amounted to about 130 students. Prerequisite analysis test includes normality test, multicollinearity test, and heteroscedasticity test. The data analysis technique used multiple linear regression analysis techniques. The results of this study financial awards have a negative and insignificant effect on the interest in choosing a profession as a public accountant. Professional training has a negative and insignificant effect on interest in choosing a profession as a public accountant. Social values ​​have a positive and significant effect on interest in choosing a profession as a public accountant. The work environment has a positive and significant effect on the interest in choosing a profession as a public accountant.. Labor market considerations have a positive and significant effect on interest in choosing a profession as a public accountant, and there is an effect of financial rewards, professional training, social values, work environment, labor market considerations together have a significant effect on the interest in choosing a profession as a public accountant in undergraduate students of Accounting Faculty of Economics and Business, Dharma Andalas University ABSTRAK Penelitian ini bertujuan untuk mengetahui dan menganalisis : (1) pengaruh penghargaan finansial terhadap minat memilih profesi sebagai akuntan publik, (2) pengaruh Pelatihan profesional terhadap minat memilih profesi sebagai akuntan publik, (3) pengaruh Nilai-nilai sosial terhadap minat memilih profesi sebagai akuntan publik, (4) pengaruh Lingkungan kerja terhadap minat memilih profesi sebagai akuntan publik, dan (5) pengaruh Pertimbangan pasar kerja terhadap minat memilih profesi sebagai akuntan publik. Jenis penelitian yang digunakan pada penelitian ini adalah penelitian secara kuantitatif. Penelitian ini menggunakan populasi mahasiswa S1 Akuntansi Fakultas Bisnis dan Ekonomi Universitas Dharma Andalas, Penelitian ini menggunakan sampel mahasiswa S1 Angkatan 2018,2019 Jurusan Akuntansi Fakultas Bisnis dan Ekonomi Universitas Dharma Andalas yang berjumlah sekitar 130 mahasiswa. Uji prasyarat analisis meliputi uji normalitas, uji multikolinearitas, dan uji heteroskedastistas. Teknik analisis data menggunakan teknik analisis regresi liniear berganda. Hasil penelitian ini Penghargaan finansial berpengaruh negarif dan tidak signifikansi terhadap minat memilih profesi sebagai akuntan publik.. Pelatihan professional berpengaruh negarif dan tidak signifikansi terhadap minat memilih profesi sebagai akuntan publik. nilai-nilai sosial berpengaruh positif dan signifikansi terhadap minat memilih profesi sebagai akuntan publik. Lingkungan kerja berpengaruh positif dan signifikansi terhadap minat memilih profesi sebagai akuntan publik. Pertimbangan pasar kerja berpengaruh positif dan signifikansi terhadap minat memilih profesi sebagai akuntan public, dan terdapat pengaruh penghargaan finansial, Pelatihan professional, Nilai-nilai sosial, Lingkungan kerja, Pertimbangan pasar kerja secara bersama-sama berpengaruh signifikan terhadap Minat memilih profesi sebagai akuntan publik pada mahasiswa S1 Akuntansi Fakultas Ekonomi dan Bisnis Universitas Dharma.